(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: build and validate the content of a graphic narrative on the prevention of Pressure Injury in the prone position in patients affected by the Coronavirus. Method: descriptive methodological study. For the construction of the graphic narrative, a scope review was carried out. Narrative content validation was performed by nurses working in stomatherapists in respiratory intensive care units in Santa Catarina, who responded to a form on Googleforms® with response options from disagree to agree. Data analysis was performed using the Content Validity Index, considering appropriate > 0.80%. Results: the care listed to compose the narrative were: skin assessment; keeping the skin clean and hydrated; use of pressure redistribution devices; use of silicone foams, transparent films, barrier-forming spray and silicone on bony prominences, under medical devices and on the face. The recommended position is that of the swimmer, repositioning the patient every two hours. Conclusion: the graphic narrative was valid for expert nurses whose emphasis is on preventive care in order to promote the engagement of the Nursing team in the face of the importance of Pressure Injury prevention in the care of patients with Coronavirus and prone.